Vocabulary Assessment With Tablets in Grade 1: Examining Effects of Individual and Contextual Factors and Psychometric Qualities - Dujardin, Emilie; Ecalle, Jean; Auphan, Pauline; Gomes, Christophe; Cros, Laurent; Magnan, Annie (Frontiers in Education, 2021)
A tablet application was designed to assess children’s receptive vocabulary in French using a classical four-choice picture paradigm and 240 words which varied in word frequency. Results showed 1) an effect of socio-demographic zone, with lower correct response scores and longer reaction times for children in disadvantaged areas, 2) an effect of word frequency, with higher correct response scores and shorter reaction times for frequent words than for rare words, and 3) an effect of age and gender on correct responses in favor of girls and older children. More interestingly, an interaction effect on correct responses revealed that for rare words, the difference between girls and boys was higher, again in favor of girls, in the normal socio-demographic zones. We used an Item Response Theory analysis to examine the psychometric qualities of each item. This then allowed us to select two shortened equivalent versions of the test which were very closely matched to certain psychometric properties. In the same way as other reading-related skills assessed using new technologies (computer or tablet), receptive vocabulary with its two parameters of speed and accuracy can be integrated as an important component of reading ability.